2019
DOI: 10.1182/blood-2019-128096
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 Multicenter Study of Tazemetostat, an EZH2 Inhibitor, in Patients with Relapsed or Refractory Follicular Lymphoma

Abstract: Introduction: Relapsed/refractory (R/R) follicular lymphoma (FL) remains a difficult-to-treat condition, with limited treatment options. New, tolerable treatments with unique mechanisms of action are needed, especially for high-risk patients whose disease progresses within 24 months of diagnosis (POD24). The epigenetic regulator EZH2 catalyzes the histone 3 lysine 27 trimethylation (H3K27m3) gene suppressive mark, which is essential for BCL6-driven germinal center (GC) formation. Conversely, a reduction in EZH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 0 publications
0
34
0
2
Order By: Relevance
“…Our findings will most likely gain special importance in the context of EZH2 targeted therapies currently being evaluated in clinical trials and may serve as a basis for a regular disease monitoring approach in the near future. The selective EZH2 inhibitor tazemetostat demonstrated objective response rates in 77% of FL patients with EZH2 mutations in an ongoing phase II clinical trial [44], with EZH2 mutations detected in both tumor tissue and plasma representing the only predictive biomarker of therapy response [45].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings will most likely gain special importance in the context of EZH2 targeted therapies currently being evaluated in clinical trials and may serve as a basis for a regular disease monitoring approach in the near future. The selective EZH2 inhibitor tazemetostat demonstrated objective response rates in 77% of FL patients with EZH2 mutations in an ongoing phase II clinical trial [44], with EZH2 mutations detected in both tumor tissue and plasma representing the only predictive biomarker of therapy response [45].…”
Section: Discussionmentioning
confidence: 99%
“…and 34% in the wild-type EZH2 cohort, with a very good safety profile. 97 Median PFS for the EZH2 mutated cohort was 11.1 months with response duration greater than 12 months observed in 33% of patients.…”
Section: Bcl2 Inhibitormentioning
confidence: 91%
“…8 Recently, updated results from a Phase II study in R/R FL reported a 77% ORR in the EZH2-mutated group, and a 34% ORR in the EZH2-wild-type group, with a median PFS of 11Á1 and 5Á7 months respectively. 61 Tazometostat is generally well tolerated, with low rates of Grade 3 or 4 AEs, the most common Grade 1/2 AEs being asthenia (33%), nausea (20%), anaemia (14%), muscle spasms (14%) and thrombocytopenia (11%). 40 It has recently received FDA approval for epithelioid sarcoma and been granted priority review for FL.…”
Section: B-cell Non-hodgkin Lymphomasmentioning
confidence: 98%